2011
DOI: 10.1111/j.1365-2699.2011.02592.x
|View full text |Cite
|
Sign up to set email alerts
|

Forest composition in Mediterranean mountains is projected to shift along the entire elevational gradient under climate change

Abstract: Aim Species distribution models have been used frequently to assess the effects of climate change on mountain biodiversity. However, the value and accuracy of these assessments have been hampered by the use of low-resolution data for species distributions and climatic conditions. Herein we assess potential changes in the distribution and community composition of tree species in two mountainous regions of Spain under specific scenarios of climate change using data with a high spatial resolution. We also describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
84
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(97 citation statements)
references
References 88 publications
(96 reference statements)
8
84
0
5
Order By: Relevance
“…The alteration of conditions at a local level can be lethal for P. sylvestris subsp. nevadensis, which can be replaced by P. nigra (Benito, et al, 2006;Garzón, et al, 2008) due to the better adaptation of this species to the continental and relatively xeric conditions of the Betic Cordillera climate, something that is also expected to happen in other northern mountains of the Iberian Peninsula (Ruiz-Labourdette, et al, 2012). López and Camacho (2010) have estimated an 85% decline in the potential area of P. sylvestris in Spain, dropping from 84,447 km² under current climate conditions to only 12,691 km² under the predicted conditions in 2050 (based on the regionalised scenarios of climate change on Spain, Morata, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The alteration of conditions at a local level can be lethal for P. sylvestris subsp. nevadensis, which can be replaced by P. nigra (Benito, et al, 2006;Garzón, et al, 2008) due to the better adaptation of this species to the continental and relatively xeric conditions of the Betic Cordillera climate, something that is also expected to happen in other northern mountains of the Iberian Peninsula (Ruiz-Labourdette, et al, 2012). López and Camacho (2010) have estimated an 85% decline in the potential area of P. sylvestris in Spain, dropping from 84,447 km² under current climate conditions to only 12,691 km² under the predicted conditions in 2050 (based on the regionalised scenarios of climate change on Spain, Morata, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been found that the specific leaf area is lowest for the Spanish provenances of P. sylvestris in comparison with other Eurosiberian provenances, which is related to the droughts and dry periods (MacAllister, 2016). In particular, in the Iberian Peninsula these forests took refuge in certain high mountain regions after their regression since the end of the Last Glacial Maximum (Ruiz-Labourdette, et al, 2012), where they currently form the western and southernmost limits of the natural distribution range of P. sylvestris (Mason, Alía, 2000;Andreu, et al, 2007;Martínez-Vilalta, et al, 2008). These circumstances have favoured its disjunct distribution in several Spanish mountain ranges and the development of five subspecies derived from two different Iberian haplotypes that existed during the Würm period (Cheddadi, et al, 2006): catalaunica Gaussen and olivicola Vayr (NE Iberian mountains), iberica Svoboda (Central and Iberian Cordilleras), pyrenaica Svoboda (central and western Pyrenees), and nevadensis (Christ) Heywood (Betic Cordillera, southern Iberian Peninsula).…”
Section: Introductionmentioning
confidence: 99%
“…Los modelos de idoneidad climática o topo-climática sintetizan, en principio, el efecto a largo plazo de la mayoría de factores considerados en los párrafos anteriores, y predicen una reducción drástica (~90%) del hábitat adecuado para el pino albar en la Península Ibérica para finales del siglo XXI (Benito-Garzón et al 2008;Keenan et al 2011;Ruiz-Labourdette et al 2012). Estos mismos modelos sugieren que al menos un 25% de las zonas actualmente ocupadas por el pino albar podrían dejar de ser habitables para la especie en el periodo 2050-2080, manteniéndose la zona de Pirineos como único gran núcleo de distribución (Keenan et al 2011).…”
Section: Figura 3 Mapas Que Muestran El Crecimiento La Mortalidad Yunclassified
“…Esto es debido a la progresiva degradación de sus nichos ecológicos, tanto por la mayor templanza y sequedad climáticas tras el último máximo glacial en Europa, como por la intensa presión antrópica a la que se ha sometido a la especie y sus há-bitats forestales desde el Neolítico reciente a la actualidad, siendo uno de los árboles más afectados por la intervención humana (Svenning y Magard 1999). Bajo estas circunstancias, la regresión de las poblaciones de T. baccata ha sido especialmente notable en la Cuenca Mediterránea: el detrimento de los bosques húmedos eurosiberianos (hayedos, robledales y abetales) -de los que el tejo comúnmente forma parte-, ha ido acompañado de una importante expansión de las formaciones esclerófilas (Ruiz-Labourdette et al 2012). En la actualidad, el déficit de agua es el factor que dirige su extensión y distribución geográfica en este territorio (Sanz et al 2009), limitándose a ambientes hú-medos en cotas progresivamente más elevadas de las principales cordilleras (Thomas y Polwart 2003, García et al 2000.…”
Section: Introductionunclassified